OPTIMIZATION OF PARAMATERS OF GRINDING WITH DIAMOND WHEELS MADE OF NICKEL-COATED DIAMOND POWDERS - Lapenko, H. O.; Horbenko, O. V.; Lapenko, T. H.; Kovtun, V. A. (Scientific Progress & Innovations, 2020)
The creation of high-performance machines and equipment characterized by high reliability and durability is justified by using new tools, which ensure the necessary accuracy and quality of machines details and equipment at their manufacturing. Tools made of synthetic diamonds meet these requirements most of all. Simultaneously with introducing synthetic diamonds in the industry the question arises concerning their more rational using, first of all, increasing tool-life and the possibility of increasing the productivity of machine processing. Tool durability is mainly determined by the quality of diamond grains and the stability of their fixation. The firmness of retaining diamond content in operating layer can be increased by using adhesive-active bonds or by creating coatings on diamond powders, which have high adhesion to diamond surface and bonds. During the study, the process of grinding and grinding wheels of 12А2 – 45⁰ shape with AC5C 125/100 powder without coating and with H12 nickel coating on BI-13 organic bond, produced by Private Joint-Stock Company “Poltava Artificial Diamond Tool” was investigated. The aim of the research was to optimize the parameters of grinding with nickel-coated diamond powder wheels to ensure high quality and accuracy of details’ machining. Experimental studies were conducted in the laboratories of Poltava State Agrarian Academy and Private Joint-Stock Company “Poltava Artificial Diamond Tool” on 3Г71 universal flat-grinding machine. Surface roughness at grinding with nickel-coated and without coating diamond wheels at different modes was determined by using shop shape-meter of model 253. Cutting modes at grinding were chosen in such a way as to ensure high productivity and necessary roughness of the finished surface at the least cos. The wheel speed was chosen maximally permissible because, thus, the productivity increased and machined surface roughness decreased. Having analyzed the obtained data it is possible to make the following conclusions: 1. The conducted studies of grinding wheels of 12А2 – 45⁰ shape with AC5C 125/100 powder with H12 nickel coating on BI-13 organic bond and wheels without nickel coating have shown that the highest grinding coefficient is achieved at 26 m/sec speed of wheel rotation. 2. Investigations were held concerning the effect of coating metallization degree of diamond powders on diamond specific consumption. It has been established that the durability of diamond wheels made with H12 nickel coating in BI - 13 bond is 1.4… 1.7 times higher in comparison with non-metallized diamond powder wheels. 3. Diamond specific consumption is decreased in nickel-coated diamond wheels with increasing metallization degree of the coating. 4. The cost of nickel-coated diamond powder wheels in comparison with uncoated wheels at grinding is decreased by 20 %. 5. The results of experimental studies have shown that nickel-coated diamond wheels manufactured in Private Joint-Stock Company “Poltava Artificial Diamond Tool” ensure high productivity, durability, high grinding coefficient, and are also less expensive than similar wheels produced abroad.